Description of the larva of Adicella cremisa Malicky 1972 and a larval key to Central European species of Adicella McLachlan 1877 (Trichoptera: Leptoceridae) - Graf, Wolfram; Waringer, Johann; Dürregger, Alexander; Vitecek, Simon (Zootaxa, 2018)
This contribution describes the previously unknown larva of Adicella cremisa Malicky 1972. Information on the morphology of the 5th larval instar is given and the important diagnostic features are highlighted on micrographs. Within the genus Adicella the hitherto known larvae differ in color patterns of the head capsule, the morphology of the posterior process of abdominal segment I, and in setation patterns on the metanotum, metasternum, abdominal segment IX, and anal prolegs. With respect to zoogeography, A. filicornis and A. reducta are widespread throughout Europe whereas A. cremisa is restricted to European Ecoregions 3 (Italian Mainland), 5 (Dinaric Western Balkan: Slovenia, Croatia), 9 (Central Highlands: Austria) and 11 (Hungarian Plains; Vienna). Based on mandible morphology, A. cremisa is likely a collector-gatherer and shredder.